Description of a new species of Anthaxia Eschscholtz, 1829 from Jordan, with notes on the Anthaxia winkleri species-group (Coleoptera, Buprestidae) - Baiocchi, Daniele; Magnani, Gianluca (Zootaxa, 2013)
A new species of Anthaxia Eschscholtz, 1829 endemic to Jordan, Anthaxia (Haplanthaxia) nabataea sp. nov., is described and illustrated. The new taxon is compared to its most similar species, and data about its distribution, bionomy and taxo-nomic position are given, together with some notes on the Anthaxia (Haplanthaxia) winkleri species-group.